EKSISTENSI DISABILITAS DALAM PROFESIONALITAS KERJA PERSPEKTIF ALQURAN - nawawi marhaban; Lenni Lestari; Alfian Sani; Nur Baiti (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2019)
This article discusses the existence of disability in shaping the professional attitude of the Qur'anic perspective. By preserving the story of Abdullah bin Ummi Maktum narrated in Surat 'Abasa, the Qur'an does not differentiate between normal people and those with disabilities, and not discriminate against one another. Not only acknowledging the existence of disability, the Qur'anic concept also explains how to behave and associate with them as being responsive and courteous, other dispensations that the Qur'an gives to disability. Although people with disabilities are not physically perfect, they have certain skills and skills that can be sharpened and developed, so that it can give birth to a professional attitude of work that does not see the physical.